3-Acetyldeoxynivalenol induces pyroptosis in leydig cells via METTL3-mediated N6-methyladenosine modification of NLRP3 - Yangyun Wang; Chaoliang Shi; Wei Jiao; Xiaoxiang Wan (Ecotoxicology and Environmental Safety)
3-acetyldeoxynivalenol (3-ADON), an acetylated derivative of deoxynivalenol, is a prevalent contaminant found in food products contaminated with mycotoxins. While the toxicological effects of 3-ADON on human and animal health are well-documented, its specific impact on the reproductive system remains underexplored. In this study, we comprehensively examined the toxicological effects of 3-ADON on TM3 Leydig cells through both in vivo and in vitro experimental models. Our results demonstrate that 3-ADON exposure leads to substantial testicular damage in vivo and significantly reduces cell viability while increasing mortality in TM3 cells in vitro (P = 0.012). Mechanistic investigations further revealed that 3-ADON exposure triggers pyroptosis in TM3 cells, as evidenced by upregulation of NLRP3, activation of caspase-1, ASC, and GSDMD. Moreover, 3-ADON treatment resulted in a significant upregulation of METTL3 expression and increased global mRNA m6A modification levels. m6A sequencing and functional assays established that METTL3-mediated m6A modification of NLRP3 mRNA enhances its stability and expression. RNA immunoprecipitation (RIP) assays further demonstrated that IGF2BP1 selectively recognizes m6A-modified NLRP3 mRNA, contributing to its stabilization. Notably, IGF2BP1 was found to inhibit the recruitment of the BTG2/CCR4-NOT complex by competitively binding to PABPC1, thereby preventing the deadenylation of NLRP3 mRNA and maintaining its expression. Additionally, we identified that METTL3 also methylates and stabilizes c-MyB mRNA, which subsequently binds to the promoter region of NLRP3, thereby enhancing its transcription. Collectively, our findings reveal a novel mechanism by which 3-ADON exerts its reproductive toxicity, underscoring the pivotal role of METTL3-mediated m6A modifications in regulating Leydig cell dysfunction.